If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3h-4(2/3h-3)=2/5h-6
We move all terms to the left:
1/3h-4(2/3h-3)-(2/5h-6)=0
Domain of the equation: 3h!=0
h!=0/3
h!=0
h∈R
Domain of the equation: 3h-3)!=0
h∈R
Domain of the equation: 5h-6)!=0We multiply parentheses
h∈R
1/3h-8h-(2/5h-6)+12=0
We get rid of parentheses
1/3h-8h-2/5h+6+12=0
We calculate fractions
-8h+5h/15h^2+(-6h)/15h^2+6+12=0
We add all the numbers together, and all the variables
-8h+5h/15h^2+(-6h)/15h^2+18=0
We multiply all the terms by the denominator
-8h*15h^2+5h+(-6h)+18*15h^2=0
We add all the numbers together, and all the variables
5h-8h*15h^2+(-6h)+18*15h^2=0
Wy multiply elements
-120h^3+270h^2+5h+(-6h)=0
We get rid of parentheses
-120h^3+270h^2+5h-6h=0
We do not support ehpression: h^3
| 3x-4=2(6+7x) | | -3x+16=-29 | | 5x-9+6x=90 | | x2-8x+7=(x-1) | | (w-2)^2-63=0 | | 29=-6+1.5x+3.5x | | x^2-590x+45000=0 | | (1/3)b-2=6-(1/2)b | | 6r+2r=8+4r | | P+14=8p+56 | | 8p-5=6p+1 | | t=-16t^2+48t+3 | | 9x-18=4x-36 | | -3g^2-12g=1+g | | a/9+9=10 | | 3x+x+2x=42 | | 12x+2{15+11(-10x+14)}=4(12x-5) | | 5x-3x+18=-32 | | -8x-65=0 | | 3x+2=-55 | | -9-3x+4x-24=4 | | Y=-5x+3x+10 | | 5m/8+15=27 | | 12x+2(15+11(-10x+14))=4(12x-5) | | j4– 2= 1 | | 2xx=5 | | 12x+215+11(-10x+14)=4(12x-5) | | 7x+1+19=12x-5 | | w+2/7=13/14 | | 12-5(3r+)=17 | | 6m=12=42 | | 6.5y−19=2.5(y−4 |